The Role of Serotonin in Regulating Depression in PTSD Patients (Clinical Study) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
This study aimed to uncover the role of serotonin in regulating depression in patients with post-traumatic stress disorder (PTSD): What is the role of serotonin in regulating depression in patients with post-traumatic stress disorder? We discussed the hypotheses and concluded that serotonin plays a key role in modulating mood and reducing depressive symptoms in patients with PTSD. The study relied on a clinical approach supported by the analysis of 3 clinical cases at Aboubaker Razi Psychiatric and Mental Disorders Hospital in Annaba and psychological scales such as the Beck Depression Inventory and the Davidson Trauma Inventory.The results found a negative correlation between low serotonin levels and the onset of depressive symptoms, as well as the effectiveness of pharmacological treatments that target this neurotransmitter, especially SSRIs (selective serotonin reuptake inhibitors). The study reinforced the importance of combining psychotherapy and pharmacotherapy to achieve better results.